EMPHASIS ENTREPRENEURIAL COMPETENCIES AND ETHICS FOR GLOBAL SUSTAINABILITY: (AT THE INTERNATIONAL CONFERENCE OF LAMAPPAPOLEONRO UNIVERSITY) - Wahyulis Hersya; Mislah Fakhira Nisa; Febriyanti Nur; Puji Rahma; M Afdal Tahir (Adisam Publisher, 2025)
This abstract was presented at the international conference of Lamappapoleonro University, themed